Fleksibilitas Ketenagakerjaan Pasca Undang-Undang Cipta Kerja dalam Perspektif Manajemen SDM - Azizah, Irma Nur; Deviani Dini Nurcahyani; Rafika Meilia Sari (CV. Aksara Global Akademia, 2026)
Changes in labor regulations through the Job Creation Law have brought significant changes to the employment system in Indonesia, particularly in terms of labor flexibility. This study aims to analyze labor flexibility after the implementation of the Job Creation Law from the perspective of Human Resource Management (HRM). The research method used is a qualitative approach through a literature study with thematic analysis of 16 scientific journals, books, and regulations related to labor flexibility and strategic Human Resource Management (HRM) practices. The results show that labor flexibility has positive impacts on companies in improving operational efficiency, productivity, and adaptability to market changes. However, on the other hand, such flexibility also creates several challenges, including job uncertainty, decreased job security, and reduced protection for contract and outsourced workers. From the HRM perspective, companies are required to create a balance between business interests and labor protection in order to maintain harmonious industrial relations. This study is expected to provide a more comprehensive understanding of labor flexibility as part of human resource management strategies in the post-labor deregulation era in Indonesia.